The Mediating Role of Human Resources and Internal Processes on the Relationship between Innovation Strategy and Financial Performance - Vajiheh Dehghan; Mahmoud Moeinadin; Soheila Shahrestani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Today, organizations must implement an innovation strategy supported by competent human resources and appropriate internal processes to succeed and achieve sustainable financial performance. Therefore, the present study investigates the role of innovation strategy in the financial performance of active manufacturing companies in Yazd province through human resource mediator variables and internal processes. Methodology: The present research is a descriptive survey. The study's statistical population consists of financial managers and senior accounting supervisors of production units in Yazd province; simple random sampling was used to select the sample, and 100 acceptable questionnaires were collected and analyzed. Cronbach's alpha coefficient confirmed the content validity of the questionnaires according to experts' opinions, and the reliability was confirmed using confirmatory factor analysis. Data was analyzed using structural equation modelling, SPSS 21, and smart PLS 3 software.Findings: Findings show that the innovation strategy significantly affects human resources and internal processes, but its effect on financial performance is insignificant. On the other hand, the impact of internal processes on financial performance was substantial, but human resources did not significantly affect financial performance. The results also show that the innovation strategy does not affect financial performance through human resources, but through internal processes, it has been able to affect financial performance.Originality/Value: The significant changes created in the business environment, along with the competition, have highlighted the role of managers in managing industries to improve the organization's performance. Theoretically, contingency theory supports the relationship between innovation and performance by explaining the role of organization design. The role of human resource capability and internal processes can also be influential in this regard. Therefore, according to the research gap in the previous studies, the present study investigated the relationship between innovation strategy and financial performance with the mediating role of human resources and internal processes at the level of industrial units in Yazd province as one of the country's industrial hubs.